Development of Partial Environmental Load Factor for Design of Tubular Joints of Offshore Jacket Platforms in Malaysia - Sambu Potty, Narayanan (2013)
The reliability analysis methods have been effectively applied to develop load and resistance factor design (LRFD) codes, such as the ISO 19902, that provide optimum structural safety taking into account the uncertainties of both the load and resistance parameters. Although, these methods have been developed since the early 1960’s their application in the design of offshore structures is still not extensive. This paper presents the procedure for reliability analysis and evaluation of the environmental load factor for design of tubular joints of offshore platforms in Malaysia, for the proposed ISO. The uncertainties affecting the joints’ resistance and loading were investigated and their statistical parameters presented. The reliability indices of a platform designed using both API RP2A – WSD and ISO 19902 were evaluated and compared. The partial environmental load factor of 1.29 was obtained, which provides a significant reference towards the adoption of ISO in Malaysia.